Greenhouse and Field Evaluation of Two Biopesticides Against Tetranychus urticae and Panonychus ulmi (Acari: Tetranychidae) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
The mycopesticide Naturalis (based on Beauveria bassiana strain ATCC 74040) and botanical pesticide Kingbo (based on oxymatrine, an alkaloid from Sophora flavescens, a traditional Chinese herb) were tested against two-spotted spider mite (Tetranychus urticae) in greenhouse vegetables and European red mite (Panonychus ulmi) in apples. These biopesticide products were applied twice at an interval of 5 days, at 0.1% and 0.2% concentrations, and their effectiveness was compared to abamectin-based products, and the synthetic acaricides acrinathrin and spirodiclofen, applied once at their recommended rates. The mycopesticide Naturalis, applied at 0.1% concentration against T. urticae in cucumber, reduced population density by 85-86%, achieving 91-93% efficacy. In a trial on tomato, efficacy reached some 96% while population density was reduced by 93%. In a field trial on apple, Naturalis showed increasing and long-lasting effectiveness against the summer population of P. ulmi: nearly 100% efficacy and population reduction were achieved in assessments  30 days after the first treatment . Naturalis applied at a double rate achieved a somewhat better effect but only in the first trial. The botanical pesticide Kingbo, applied at 0.1% concentration, demonstrated very high control efficacy (≥98%) and population density reduction (≥96%) of T. urticae in both trials. A high and long-lasting effectiveness of this bioacaricide was achieved in a trial on P. ulmi. A 0.2% concentration achieved similar effect. The results in these trials indicate that applications of the mycopesticide Naturalis and botanical pesticide Kingbo can provide effective control of T. urticae on cucumber and tomato grown in greenhouses, as well as P. ulmi on apple.